Հայ որբատած հաստատութիւնների գործունէութեան կազմակերպումն Արեւելեան Հայաստանում եւ Անդրկովկասում 1914—1917 թթ. - Յարութիւնեան, Աւետիս; Բալեան, Արշակ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье обобщено огромное количество информации из архивных материалов, мемуаров очевидцев, свидетельств из периодической печати, а также заключений из научных исследований. Сопоставив все источники, автор пришел к важным результатам, стараясь получить правдивую картину деятельности приютов в Восточной Армении и Закавказье. The article summarizes a great amount of information from archival materials, memoirs of eyewitnesses, testimonies from periodicals, as well as conclusions from scientific researches. By comparing all the sources, the author came to important results, trying to get a true picture of the activity of orphanages in Eastern Armenia and Transcaucasia.
Keywords: Հայոց պատմութիւն